Effects of dietary enzymes or specialty proteins on nursery pig performance - Jones, Cassandra Katherine (Kansas State University, 2009)
Eight experiments used 1,712 pigs to determine influences of dietary enzymes or specialty proteins on nursery pig performance. Experiments 1 and 2 evaluated the effects of fish meal, fermented soybean meal, or dried porcine solubles on performance. Experiment 1 showed pigs fed dried porcine solubles had improved (P = 0.01) ADG and G:F compared to pigs fed the control diet, and improved (P = 0.03) G:F compared to pigs fed the combination of fermented soybean meal and fish meal. Experiment 2 showed pigs fed increasing fermented soybean meal had improved (quadratic, P = 0.03) G:F. Experiments 3 and 4 evaluated the effects of commercial enzyme addition to diets containing dried distillers grains with solubles (DDGS) on performance. In experiment 3, neither DDGS nor enzyme addition influenced (P > 0.10) ADG and G:F. Experiment 4 found there were no (P > 0.32) enzyme × DDGS source interactions. Corn DDGS did not influence pig performance (P > 0.36). Sorghum DDGS reduced (P = 0.003) G:F, with no difference between sorghum DDGS sources. Adding enzymes to 30% DDGS diets did not improve (P > 0.57) performance. Experiments 5 and 6 evaluated the effects of fish meal (SMFM), spray-dried animal plasma (SDAP), or peptone on performance. In Experiment 5, different specialty proteins had similar (P > 0.10) ADG, ADFI, or G:F. Experiment 6 showed pigs fed 4% Peptone 2 during phase 1 and 2% Peptone 2 during phase 2 had improved (P < 0.05) ADG compared to pigs fed SMFM, and improved (P < 0.05) G:F compared to pigs fed all other diets. Experiments 7 and 8 developed an available P release curve for commercial phytase products. In both experiments, pigs fed increasing inorganic P had improved (linear, P < 0.01) G:F and percentage bone ash. Pigs fed increasing OptiPhos 2000-M, Phyzyme XP, or Ronozyme P had improved (P < 0.001) percentage bone ash. Available P release for up to 1,000 FTU/kg of Escherichia coli-derived phytases can be predicted by the equation (y = -0.000000125x[superscript]2 + 0.000236245x + 0.015482), where x is the phytase level in the diet.
Keywords: Dietary enzymes; Nursery pig; Specialty proteins; Agriculture, Animal Culture and Nutrition (0475)